TREATMENT OUTCOME OF PULMONARY TUBERCULOSIS IN A TEACHING REFERRAL CLINIC, IN IRAN - Jamshid Ayatollahi; Fatemeh Amighi; Mohammad Reza Sharifi et al. (Journal of University Medical & Dental College, 2014)
ABSTRACT: OBJECTIVES: Tuberculosis is an endemic infection in Iran. Despite improved living standards and availability of free drugs, tuberculosis remains a major health problem in Iran. In this study, we assessed the treatment outcome of tuberculosis patients. METHODS: In this descriptive study, all new cases of pulmonary tuberculosis with smear or culture positive admitted in Niko poor referral clinic, in Yazd, Iran were studied. RESULTS: Of the 280 patients, 148 (52.9%) were males and 132 (47.1%) were females. Among these patients 202 (72.2%) had pulmonary smear positive tuberculosis and 78(27.8%) patients had smear negative pulmonary tuberculosis? Treatment outcome was 247 (90.8%) successful treatment,3 (1.1%) treatment failure, 10 (3.7%) treatment defaultures,9 (3.3%) died and 3 (1.1%) transferred to a different area. CONCLUSIONS: In our study cure rate among new smear positive patients was more the rate recommended by the world health organization.